Diffusion of mobile phones in Portugal: unexpected success? - Carvalho, Adão (2013)
This paper begins with a somewhat paradoxical situation: Portugal is one of the less innovative countries within the European Union by most innovation indicators but, simultaneously, it is a leading country in the diffusion of mobile phones. The remarkable evolution of the mobile telecommunications sector over the last 15 years turns the issue a little more intriguing. This paper addresses the diffusion of mobile phones in Portugal and focuses particularly on the take-off stage, which signalled a sudden change in the pattern of diffusion. The introduction of an innovation – prepaid cards – explains most of the change in the diffusion curve occurred around 1996 and the subsequent increase in the penetration rate. Prior known research has not considered pre-paid cards an important determinant of mobile phone diffusion, but pre-paid services had an enormous impact on the rate of adoption of mobile phones in many countries and it is the major take-off determinant of mobile phone diffusion in Portugal. The time lag between the launching of this innovation in Portugal and its adoption by other EU countries explains why Portugal not just caught up with the EU average mobile phone penetration rate around 1996, but moved ahead of it from then on.